Pharmacological strategies to overcome immune checkpoint inhibitor resistance in non-small cell lung cancer - Xu, Yuyu; Shen, Huiling; Shang, Dong; Zhu, Cailin (Frontiers in Oncology, 2026)
Immune checkpoint inhibitors (ICIs) have redefined the therapeutic paradigm of non-small cell lung cancer (NSCLC), offering durable remission in select patients by reactivating anti-tumor T cell responses. Yet, this clinical triumph is tempered by the reality that most patients experience either primary resistance or relapse due to acquired resistance, underscoring an urgent need for mechanistically grounded solutions. Resistance arises through a complex interplay of tumor-intrinsic mechanisms, including defects in antigen presentation, interferon signaling disruption, and oncogenic pathway activation (EGFR, KRAS, MET), and tumor-extrinsic factors such as immunosuppressive cell populations, inhibitory cytokines, and metabolic rewiring of the tumor microenvironment (TME). This review provides a comprehensive synthesis of emerging pharmacological strategies aimed at reversing ICI resistance in NSCLC. Promising avenues include dual or multi-checkpoint inhibition (targeting LAG-3, TIGIT, TIM-3), integration of epigenetic reprogrammers to resensitize immune-silent tumors, and metabolic interventions that normalize the TME. Additionally, combination regimens with oncogene-directed therapies, engineered cytokine analogs, neoantigen-based vaccines, and adoptive T cell therapies are reshaping the frontier of immunoresistant NSCLC management. We also highlight pivotal clinical trials—both completed and ongoing that illuminate translational breakthroughs and therapeutic pitfalls. Looking ahead, the field must grapple with key challenges: the refinement of predictive biomarkers, stratification of patients through genomic, immunologic, and microbiome-based profiling, and the management of toxicity in complex combination protocols. Ultimately, a shift toward highly personalized, biomarker-guided therapeutic strategies holds the greatest promise for overcoming resistance and extending the reach of immunotherapy in NSCLC.